Riwayat paparan pestisida dan kekurangan asupan zat gizi sebagai faktor risiko kejadian anemia pada ibu hamil di daerah pertanian - Sulistyawati, Sulistyawati; Margawati, Ani; Rosidi, Ali; Suhartono, Suhartono (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2019)
Background: Anemia in pregnant women in Brebes Regency, Central Java in 2016 was still high at 60.7%. Brebes Regency is an area of onion farming with a high intensity of pesticide use. Objectives: This study aimed to prove the history of pesticide exposure and lack of nutrient intake (iron and vitamin C) was risk factor for the incidence of anemia in pregnant women in agricultural area. Methods: Case control study with 41 cases (anemia) and 41 controls (non-anemia) as study subjects. The subjects were selected using purposive sampling method. Pesticide exposure history included the involvement of pregnant women in agricultural activities, frequency of exposure and length of exposure was measured by interview using structured questionnaire. Anemia data were obtained by measuring hemoglobin levels. Other independent variables measured were nutritional intake (protein, iron, and vitamin C) using semi-quantitative food frequency questionnaire (SQ-FFQ) method to determine the level of nutrient adequacy in pregnant women. Data were analyzed using chi-square test and logistic regression.Result: Hemoglobin levels in the case ranged from 7.2 g/dl to 10.9 g/dl. The results of multivariate logistic regression showed that pesticide exposure history (OR= 4.9, 95% CI:1.75-13.67), level of iron adequacy (OR = 2.9, 95% CI:1.06– 8.29) and level of vitamin C adequacy (OR = 3.4, 95% CI:1.10– 10.28) as risk factors for the incidence of anemia in pregnant women in agricultural area.Conclusion: The history of pesticide exposure and lack of nutrient intake (iron and vitamin C) was risk factor for the incidence of anemia in pregnant women in agricultural area.